Together or separate? Contributions from neuroeducation to the debate on sex segregation in schools - Reverter, Sonia (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
This article analyses the debate on the desirability of separating children by sex in schools. The study reviews the neuroscientific arguments that can inform decisions on this issue. The author starts from the understanding that the education debate should centre its decision not on neuroscientific findings, which are still inconclusive, but on a proposal that evaluates the aim of education. As a new field of study, neuroeducation has the opportunity to draw into the dialogue all the disciplines participating to that end.
Keywords: neuroeducation; single sex education; co-education; sex difference